RCRR STRATEGY: IS IT EFFECTIVE TO IMPROVE STUDENTS’ READING COMPREHENSION ACHIEVEMENT? - Eny Erianti; Merie Agustiani; Mila Arizah (Program Studi Pendidikan Bahasa Inggris - Fakultas Keguruan dan Ilmu Pendidikan - Universitas Baturaja, 2022)
This study aimed at improving the tenth grade students’ reading comprehensionachievement by using RCRR Strategy. The design of this study was quasi experimentalresearch.The tenth grade students from X TKJ 1 and X TKJ 2 which consisted of 72students were taken as the sample in this study through purposive sampling. The data werecollected using 20 multiple-choice questions of reading comprehension test. Thedataanalyzed by statistic formula of T-test. Based on findings, the students’ pre test mean scorein experimental class was 55,83 and after that the students’ post test mean score was 82,64.The testing of hypotheses also proved that RCRR strategy gave significant effect onstudents’ reading comprehension on the sig (2 tailed) value was 0,025 (<0.005). From theresult it can be concluded that there was a significance different on tenth grade students’reading comprehension achievement on experimental and control class of SMK Negeri 1OKU.